2024
DOI: 10.1101/2024.05.19.594864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Control of Inhibitory and Excitatory Nerve Terminal Function by Mitochondria

Kirsten Bredvik,
Timothy A. Ryan

Abstract: Inhibitory neurons shape the brain's computational landscape and rely on different cellular architectures and intrinsic properties than excitatory neurons. Maintenance of the overall balance of excitatory (E) versus inhibitory (I) drive is essential, as disruptions can lead to neuropathological conditions, including autism and epilepsy. Metabolic perturbations are a common driver of E/I imbalance but differential sensitivity of these two neuron types to metabolic lesions is not well understood. Here, we charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
3
1
0
Order By: Relevance
“…Given the similarity of resting ATP levels between neurons in BHB and neurons in lactate/pyruvate ( Figure 2A , Supplementary Figure 2A ), we examined iATPSnFR2.0-HALO fluorescence recovery following a burst of AP firing capable of transiently depressing presynaptic ATP levels, for neurons bathed in either BHB or lactate/pyruvate. Following a 60 second burst of 10 Hz AP firing, presynaptic ATP recovered much more slowly in excitatory compared to inhibitory neurons when fueled by lactate/pyruvate ( Figure 2C – E ), as previously reported ( Bredvik and Ryan, 2024 ). Inhibitory neurons in BHB recovered much more slowly than inhibitory neurons in lactate/pyruvate ( Figure 2B – 2D ).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Given the similarity of resting ATP levels between neurons in BHB and neurons in lactate/pyruvate ( Figure 2A , Supplementary Figure 2A ), we examined iATPSnFR2.0-HALO fluorescence recovery following a burst of AP firing capable of transiently depressing presynaptic ATP levels, for neurons bathed in either BHB or lactate/pyruvate. Following a 60 second burst of 10 Hz AP firing, presynaptic ATP recovered much more slowly in excitatory compared to inhibitory neurons when fueled by lactate/pyruvate ( Figure 2C – E ), as previously reported ( Bredvik and Ryan, 2024 ). Inhibitory neurons in BHB recovered much more slowly than inhibitory neurons in lactate/pyruvate ( Figure 2B – 2D ).…”
Section: Resultssupporting
confidence: 86%
“…One notable finding is that under pure BHB conditions, inhibitory neurons sustain much higher steady-state presynaptic ATP levels than excitatory neurons (Figure 2A), consistent with our previous observation that there is a higher abundance of mitochondria in inhibitory neurons (Bredvik and Ryan, 2024). We found that although both subtypes could cell autonomously use BHB as a fuel for synaptic transmission, in the stimulus paradigms examined (10 Hz firing in bursts at minute intervals or sustained for 60 seconds) inhibitory neurons performed no better than excitatory neurons when provided BHB as fuel (Figure 1, Figure 3, Supplementary Figure 1, Supplementary Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations